2014
DOI: 10.1007/s00223-014-9941-9
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Anthropometry and Body Composition on Children’s Bone Health: The Childhood Health, Activity and Motor Performance School (The CHAMPS) Study, Denmark

Abstract: Overweight, physical inactivity and sedentary behaviour have become increasing problems during the past decade. Increased sedentary behaviour may change the body composition (BC) by increasing the fat mass relative to the lean mass (LM). These changes may influence bone health to describe how anthropometry and BC predict the development of the bone accruement. The longitudinal study is a part of The CHAMPS study-DK. Children were DXA scanned at baseline and at 2-year follow-up. BC (LM, BF %) and BMC, BMD and B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 25 publications
3
20
1
Order By: Relevance
“…Obesity during childhood was associated with increased vertebral bone density and increased whole body bone mass [45]. Moreover, CBMI can predict bone mineral accrual and bone size positively and independently [44]. Additionally, we also observed the positive genetic correlation between ABMI and CBMI.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Obesity during childhood was associated with increased vertebral bone density and increased whole body bone mass [45]. Moreover, CBMI can predict bone mineral accrual and bone size positively and independently [44]. Additionally, we also observed the positive genetic correlation between ABMI and CBMI.…”
Section: Discussionsupporting
confidence: 55%
“…Childhood is crucial period for bone growth, accounting for about half of the bone mass achieved in adulthood [43]. Thus, CBMI can be used as a determinant for adult bone mass and the BMD values [4446]. Obesity during childhood was associated with increased vertebral bone density and increased whole body bone mass [45].…”
Section: Discussionmentioning
confidence: 99%
“…Others have suggested that fat mass positively predicts either bone size in isolation [73], or improves bone size and mineral content independently during early childhood [71]. Whatever the influence of fat mass on skeletal development, bone mass and additionally bone strength are more strongly influenced by an increase in lean mass in overweight children [64, 74]. However, stating that excess fat mass in childhood has a negative or positive impact on skeletal development may well be overly simplistic and outcomes may vary according to age and pubertal development.…”
Section: Longitudinal Impact Of Fat Mass On Bone Health During Skeletmentioning
confidence: 99%
“…We additionally found, by handsearch, 3 relevant studies. From these 1892 articles, after a long process of review and discussion (Figure 1), fifteen studies were finally included [11,22,[25][26][27][28][29][30][31][32][33][34][35][36][37], detailed as follows: -10 studies examining the link between evolution of lean mass and evolution of bone mass; -4 studies focusing on the link between evolution of muscle strength and evolution of bone mass; -1 study dealing with the link between evolution of physical performance and evolution of bone mass.…”
Section: Rendering Of Our Literature Searchmentioning
confidence: 99%
“…The population of interest was children for 5 studies [25][26][27]31,32], and the population of interest of the other studies were in female around the menopause age or the older age. With regards to the gender of the participants, 10 studies only focused on female subjects, 2 studies on male subjects only [27,38], and 3 other studies consisted of a population of both men and women [31, 32,36]. The duration of follow-up of these longitudinal studies ranges from 1 year to 10 years.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%